The effects of season and meteorology on human mortality in tropical climates: a systematic review - Burkart, Katrin; Khan, Md. Mobarak Hossain; Schneider, Alexandra; Breitner, Susanne; Langner, Marcel; Krämer, Alexander; Endlicher, Wilfried (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2014)
Research in the field of atmospheric science and epidemiology has long recognized the health effects of seasonal and meteorological conditions. However, little scientific knowledge exists to date about the impacts of atmospheric parameters on human mortality in tropical regions. Working within the scope of this systematic review, this investigation conducted a literature search using different databases; original research articles were chosen according to pre-defined inclusion and exclusion criteria. Both seasonal and meteorological effects were considered. The findings suggest that high amounts of rainfall and increasing temperatures cause a seasonal excess in infectious disease mortality and are therefore relevant in regions and populations in which such diseases are prevalent. On the contrary, moderately low and very high temperatures exercise an adverse effect on cardio-respiratory mortality and shape the mortality pattern in areas and sub-groups in which these diseases are dominant. Atmospheric effects were subject to population-specific factors such as age and socio-economic status and differed between urban and rural areas. The consequences of climate change as well as environmental, epidemiological and social change (e.g., emerging non-communicable diseases, ageing of the population, urbanization) suggest a growing relevance of heat-related excess mortality in tropical regions.